Impacts of tourism growth towards the development of Melaka / Nur Shazilawati Md Zooki (Faculty of Business and Management, 2008)
Tourisms are one of the most important economic activities in a country. For Malaysia, tourism industry has developed extremely and it has contributed to the economic growth. This tourism industry also has contributing to a third to a half of GOP in most countries whereby Carribean countries rely on their natural environment as the main lure to visitors (Environment Department The World Bank, 2000). For the past several years, Melaka has expanded their tourism industry and tourism has become one of the major sectors that contribute to the economic growth of the state. With the attraction from the historical places in Melaka, this state has received a huge number of tourist arrivals. Because of this, the revenues of Melaka can be increased. The purpose of this study is to identify which impacts that can contribute to the increase of Melaka state revenues since Melaka's mission and objectives is to become fully industrialized in 2010. This study also will determine factors that will influence the development of Melaka.